The Implementation Of Pertamina Safety Approval (Psa) And Training On Work Safety Mediated By Safety Culture On Board The Fleet Of Ships Owned By PT. XYZ Shipping: English - Agung Kwartama; Lie Adek (Cita konsultindo, 2024)
Pertamina Safety Approval (PSA) is a document that shows when a ship has met the standards and criteria of the vetting inspection results whereas safety departement prepare before vessel departured. The research aims to determine the effect of implementing Pertamina Safety Approval (PSA) and safety training on work mediated by safety culture on PT's fleet of ships. XYZ. The research method uses an explanatory quantitative approach. The total sample is 90 respondents who have a PSA and are on board in 2022. The analysis tools used are SPSS and SEMPLS. The research results show that there is a direct and indirect influence between the implementation of Pertamina Safety Approval (PSA) and safety training on work safety mediated by safety culture on company's fleet of ships. XYZ